Hubungan Keteraturan Kunjungan Antenatal Care (ANC) Dengan Kejadian Anemia Pada Ibu Hamil: The Relationship Between Regularity of Antenatal Care (ANC) Visits and the Incidence of Anemia in Pregnant Women - efendi, Aprilianti mayang; Wulandatika, Darmayanti; Azhari, Fahrin; Ulfa, Siti Maria (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Anemia during pregnancy remains a significant public health problem because it increases the risk of maternal and fetal complications. Regular antenatal care (ANC) visits are important for early detection and prevention of anemia among pregnant women. This study aimed to analyze the relationship between the regularity of ANC visits and the incidence of anemia among pregnant women at Alalak Selatan Community Health Center, Banjarmasin. This quantitative study used a cross-sectional design with an observational analytic approach. The sample consisted of 30 third-trimester pregnant women with gestational age ≥37 weeks selected using purposive sampling technique. Data were collected through maternal and child health (MCH) books and direct observation after informed consent was obtained. The independent variable was the regularity of ANC visits, while the dependent variable was the incidence of anemia among pregnant women. Data were analyzed using univariate and bivariate analysis with Fisher’s Exact Test. A total of 73.3% of respondents experienced anemia, and 56.7% had irregular ANC visits. Statistical analysis showed that there was no significant relationship between the regularity of ANC visits and the incidence of anemia among pregnant women (p = 0.242; p > 0.05). The regularity of ANC visits was not significantly associated with anemia among pregnant women. Other factors such as nutritional intake, adherence to iron tablet consumption, and maternal health behavior may contribute to the incidence of anemia during pregnancy